Inequalities about normalized Lp projection body. Issue 10 (3rd October 2021) - Tang, Zhongwen; Si, Lin
Abstract: In this paper, we establish a Loomis-Whitney type inequality about volume normalized Lp projection body for p ≥ 1 with complete equality conditions for p ̸ = 2. Meanwhile, an estimate for the weighted Lp zonoid is given.